SM50 Repeat-Polypeptides Self-Assemble into Discrete Matrix Subunits and Promote Appositional Calcium Carbonate Crystal Growth during Sea Urchin Tooth Biomineralization - Mao, Yelin (Ann Anat, 2015)
The two major proteins involved in vertebrate enamel formation and echinoderm sea urchin tooth biomineralization, amelogenin and SM50, are both characterized by elongated polyproline repeat domains in the center of the macromolecule. To determine the role of polyproline repeat polypeptides in basal deuterostome biomineralization, we have mapped the localization of SM50 as it relates to crystal growth, conducted self-assembly studies of SM50 repeat polypeptides, and examined their effect on calcium carbonate and apatite crystal growth. Electron micrographs of the growth zone of Strongylocentrotus purpuratus sea urchin teeth documented a series of successive events from intravesicular mineral nucleation to mineral deposition at the interface between tooth surface and odontoblast syncytium. Using immunohistochemistry, SM50 was detected within the cytoplasm of cells associated with the developing tooth mineral, at the mineral secreting front, and adjacent to initial mineral deposits, but not in muscles and ligaments. Polypeptides derived from the SM50 polyproline alternating hexa- and hepta-peptide repeat region (SM50P6P7) formed highly discrete, donut-shaped self-assembly patterns. In calcium carbonate crystal growth studies, SM50P6P7 repeat peptides triggered the growth of expansive networks of fused calcium carbonate crystals while in apatite growth studies, SM50P6P7 peptides facilitated the growth of needle-shaped and parallel arranged crystals resembling those found in developing vertebrate enamel. In comparison, SM50P6P7 surpassed the PXX24 polypeptide repeat region derived from the vertebrate enamel protein amelogenin in its ability to promote crystal nucleation and appositional crystal growth. Together, these studies establish the SM50P6P7 polyproline repeat region as a potent regulator in the protein-guided appositional crystal growth that occurs during continuous tooth mineralization and eruption. In addition, our studies highlight the role of species-specific polyproline repeat motifs in the formation of discrete self-assembled matrices and the resulting control of mineral growth.